1996
DOI: 10.1021/om9605185
|View full text |Cite
|
Sign up to set email alerts
|

tert-Amyl Compounds of Aluminum and Gallium:  Halides, Hydroxides, and Chalcogenides

Abstract: The reaction of AlCl 3 with 3 equiv of the tert-amyl Grignard reagent (Me 2 EtC)MgCl yields the monomeric trialkyl compound Al(CMe 2 Et) 3 (1). Reaction of compound 1 with MeCN and [PPN]Cl yields the Lewis acid-base complexes Al(CMe 2 Et) 3 (MeCN) (2) and [PPN][AlCl-(CMe 2 Et) 3 ] (3), respectively. The hydrolysis of Al(CMe 2 Et) 3 in hexane results in the formation of the trimeric hydroxide [(Me 2 EtC) 2 Al(µ-OH)] 3 (4), which is converted to the dimer [(Me 2 EtC) 2 Al(µ-OH)] 2 (5) upon heating. The reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
54
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 33 publications
10
54
0
Order By: Relevance
“…All Al 2 E 2 rings are, due to their symmetry, essentially planar, and the AlϪE bond lengths are analogous to those of similar Al 2 E 2 species (2.208Ϫ2.248 Å for S, 2.221Ϫ2.381 Å for Se, and 2.562Ϫ2.588 Å for Te), but the E(1)ϪAlϪE(1A) (E ϭ Se, [4Ϫ12] due to the steric bulk of the β-diketiminato ligand. The latter values are similar to those of Al 4 E 4 clusters (94.2Ϫ99.2°for Se and 94.1Ϫ96.3°for Te), [14,15] where the chalcogen atoms are always coordinated to three aluminum atoms. The S(1)ϪAlϪS(1A) angle fits within the range of similar compounds (95.9Ϫ101.9°).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…All Al 2 E 2 rings are, due to their symmetry, essentially planar, and the AlϪE bond lengths are analogous to those of similar Al 2 E 2 species (2.208Ϫ2.248 Å for S, 2.221Ϫ2.381 Å for Se, and 2.562Ϫ2.588 Å for Te), but the E(1)ϪAlϪE(1A) (E ϭ Se, [4Ϫ12] due to the steric bulk of the β-diketiminato ligand. The latter values are similar to those of Al 4 E 4 clusters (94.2Ϫ99.2°for Se and 94.1Ϫ96.3°for Te), [14,15] where the chalcogen atoms are always coordinated to three aluminum atoms. The S(1)ϪAlϪS(1A) angle fits within the range of similar compounds (95.9Ϫ101.9°).…”
Section: Resultssupporting
confidence: 79%
“…Thus, the [AlE] n core can be either square planar (n ϭ 2), [4Ϫ13,17] cubic (n ϭ 4) [13Ϫ17] or adopt a hexagonal drum structure (n ϭ 6). [14] Other examples containing Al and E in a ratio that deviates from 1:1 have also been reported to exhibit a bent AlϪEϪAl moiety, adamantane-like Al 4 E 6 or more complex structures. [3,20Ϫ24] We have recently shown that [LAlH 2 ] (2), prepared from LH and AlH 3 ·NMe 3 , reacts with elemental selenium [3] and, in the presence of a phosphane as catalyst, also with elemental sulfur, [2] to give species of the general formula [LAl(EH) 2 ] (E ϭ Se, S).…”
Section: Introductionmentioning
confidence: 99%
“…The X‐ray structure analysis of 1 reveals a remarkable Al 4 C 4 N 4 cage configuration in which the C atoms adopt exo positions and thus may be formally viewed as inserting into four Al−N bonds of an Al 4 N 4 cube (Figure 1 A). 9 It is surprising that a significant difference in the arrangement of the atoms within the cage skeleton of 1 is found in comparison with those of other known aluminum compounds with a 12‐membered core ((AlE) 6 , E=N,3d3g O,10a S,10b P,10c As10d) which exclusively adopt the form of a hexagonal‐prismatic array. The core of 1 consists of six faces formed by two boat‐shaped six‐membered Al 2 C 2 N 2 rings and four puckered five‐membered Al 2 CN 2 rings.…”
mentioning
confidence: 99%
“…H NMR (THF-d 8 , 235 K, δ): 7.0-8.3 (m, 5 H, C 6 H 5 ), 3.62 (m, THF), 1.77 (m, THF), 1.12 [d, 4 J( 1 H-31 P) ) 1 Hz, 18 H, N t Bu] 31. P{ 1 H} NMR (THF-d 8 , 235K, δ): -14.4 [s, 1 J( 31 P-125 Te ) 1209 Hz)].…”
mentioning
confidence: 99%